THE WAYANG WONG ANAK-ANAK PERFORMANCE DEVELOPMENT - Ruastiti, Ni Made; Rai S., I Wayan; Kharisma Pradana, Gede Yoga (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
So that the art of wayang wong in Bali can be maintained, the research team has created Wayang Wong Anak-Anak. As a vehicle for socializing cultural values, this model is very important to be developed. The development of this wayang Wong model intensively involves young Balinese people. The problems : 1) How is the process of fostering Wayang Wong Anak-Anak?; 2) What is the form of the Wayang Wong Anak-Anak?. As a result of applied research, a number of data collection have been carried out, including document studies, observations, exercises, and in-depth interviews with informants. The results : 1) The process of fostering Wayang Wong Anak-Anak has been carried out through : (a) applying the performance concepts; (b) conducting exercises to find a model of Wayang Wong Anak-Anak that suits the tastes and abilities of the youth, (c) a trial for a Wayang Wong Anak-Anak show, (d) finalizing a model for a Wayang Wong Anak-Anak; 2) the coaching in the development of wayang wong has succeeded in implementing the Wayang Wong Anak-Anak, namely : themes, variety of movements, and performances that are in accordance with the abilities and character of the youth.